Sustained delivery of siRNA/mesoporous silica nanoparticle complexes from nanofiber scaffolds for long-term gene silencing - Pinese, Coline (2018)
A low toxicity and efficient delivery system is needed to deliver small interfering RNAs (siRNA) in vitro and in vivo. The use of mesoporous silica nanoparticles (MSN) is becoming increasingly common due to its biocompatibility, tunable pore size and customizable properties. However, bolus delivery of siRNA/MSN complexes remains suboptimal, especially when a sustained and long-term administration is required. Here, we utilized electrospun scaffolds for sustained delivery of siRNA/MSN-PEI through surface adsorption and nanofiber encapsulation. As a proof-of-concept, we targeted collagen type I expression to modulate fibrous capsule formation. Surface adsorption of siRNA/MSN-PEI provided sustained availability of siRNA for at least 30 days in vitro. As compared to conventional bolus delivery, such scaffold-mediated transfection provided more effective gene silencing (p < 0.05). On the contrary, a longer sustained release was attained (at least 5 months) when siRNA/MSN-PEI complexes were encapsulated within the electrospun fibers. In vivo subcutaneous implantation and biodistribution analysis of these scaffolds revealed that siRNA remained localized up to ~290 m from the implants. Finally, a fibrous capsule reduction of ~45.8 % was observed after 4 weeks in vivo as compared to negative scrambled siRNA treatment. Taken together, these results demonstrate the efficacy of scaffold-mediated sustained delivery of siRNA/MSN-PEI for long-term non-viral gene silencing applications.